Effects of harvest restraint periods and fluctuation tolerances of profits and harvests on sustainable timber supply levels from private forests in a district. Issue 1 (2nd January 2017) - Moriya, Tomoyuki; Tatsuhara, Satoshi
ABSTRACT: The current age class distribution of plantation forests in Japan is bell-shaped, with the peak at 50 years. This offers opportunities to increase domestic timber supplies, but confidence in the long-term stability of supplies must be established. For this, greater knowledge of sustainable harvest levels starting from current stocks is required. Thus, this study analyzed effects on harvest levels of varying harvest restraint periods and fluctuation tolerances of both harvest and profit levels, focusing on privately owned Cryptomeria japonica plantations in the Sampoku district of Murakami City, Niigata Prefecture, Japan. A 0-1 integer programming model was formulated to predict maximum sustainable harvest levels from the forests that could provide stable profits. Permutations of five harvest restraint period cases and three fluctuation tolerance cases were simulated to assess effects on the volume of total harvests. A 10-year harvest restraint period dramatically increased the sustainable harvest level, but extending it further had weaker effects. Varying the fluctuation tolerances substantially affected sustainable harvest levels in the absence of harvest restraints, but not in their presence. Thus, imposing a 10-year harvest restraint period enabled maximal sustainable timber production in the study area.